2014
DOI: 10.1111/ecog.00566
|View full text |Cite
|
Sign up to set email alerts
|

Testing environmental and genetic effects in the presence of spatial autocorrelation

Abstract: Spatial autocorrelation is a well‐recognized concern for observational data in general, and more specifically for spatial data in ecology. Generalized linear mixed models (GLMMs) with spatially autocorrelated random effects are a potential general framework for handling these spatial correlations. However, as the result of statistical and practical issues, such GLMMs have been fitted through the undocumented use of procedures based on penalized quasi‐likelihood approximations (PQL), and under restrictive model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
228
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(230 citation statements)
references
References 61 publications
1
228
1
Order By: Relevance
“…The significance of fixed effects was estimated using a loglikelihood ratio test. The most common procedure used to deal with spatial autocorrelation is based on penalised quasilikelihood approximations (glmmPQL), but the assumptions underlying the autologistic regression used in this algorithm have been criticised recently (Betts et al, 2009;Rousset and Ferdy, 2014). Our preliminary analyses (results not reported) demonstrated that although penalised quasi-likelihood approximations produced similar results, the method suggested by Rousset and Ferdy (2014) was more conservative.…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…The significance of fixed effects was estimated using a loglikelihood ratio test. The most common procedure used to deal with spatial autocorrelation is based on penalised quasilikelihood approximations (glmmPQL), but the assumptions underlying the autologistic regression used in this algorithm have been criticised recently (Betts et al, 2009;Rousset and Ferdy, 2014). Our preliminary analyses (results not reported) demonstrated that although penalised quasi-likelihood approximations produced similar results, the method suggested by Rousset and Ferdy (2014) was more conservative.…”
Section: Methodsmentioning
confidence: 90%
“…We plotted Moran's I autocorrelation coefficient calculated for pairs of spatial observations against distance (5 km increment) using the ncf package (R Development Core Team 2013). Rousset and Ferdy (2014) suggested accounting for this effect when inferring fixed effects, even if autocorrelation appears nonsignificant. Generalised linear mixed models (GLMMs) were applied with spatially autocorrelated random effects and a variant of penalised quasi-likelihood approximations (PQL/ L) for the estimation of fixed effects, as recommended for binary data (Rousset and Ferdy 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite notable exceptions, it is hard to imagine a world in which the law is not true, and it provides a very useful principle for analyzing earth surface information [28]. The widespread application of geography today accommodates a variety of perspectives on the significance of this law [29,30]. Remote sensing imagery is obtained based on the radiance of specific source targets on the ground surface.…”
Section: Review Of Tobler's First Law Of Geographymentioning
confidence: 99%